Nurse-led interventions in systemic autoimmune rheumatic diseases: a systematic review - Robyn K. Wojeck; Kimberly Arcoleo; Elizabeth C. Hathaway; Tamara J. Somers (BMC, 2023)
Abstract Background Nurses play an important role in the management of patients with systemic autoimmune rheumatic diseases. Little is known about the effectiveness of nurse-led interventions on patient-reported outcomes in this population. The aim of this systematic review was to examine the evidence of nurse-led interventions in systemic autoimmune rheumatic diseases. Methods Using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, a comprehensive literature search was conducted in PubMed, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, and Embase for studies published from database inception to September 2022. Studies were included if they were published in a peer-reviewed journal in English and evaluated the effectiveness of a nurse-led intervention using a randomized controlled trial design in adults with a systemic autoimmune rheumatic disease. Screening, full-text review, and quality appraisal were conducted by two independent reviewers. Results A total of 162 articles were identified for possible inclusion, of which five studies were included. Four of five studies (80%) were conducted in systemic lupus erythematosus. There was significant variability in the types of nurse-led interventions; the majority included educational sessions and follow up counseling by a nurse (n = 4). The most common patient-reported outcomes were health-related quality of life (n = 3), fatigue (n = 3), mental health (including anxiety and depression) (n = 2), and self-efficacy (n = 2). The duration of the interventions varied from 12 weeks to 6 months. All studies included a nurse with specialized training and education and showed significant improvements in their primary outcomes. The majority of the studies (60%) were considered high methodological quality. Conclusion This systematic review provides emerging evidence for the use of nurse-led interventions in systemic autoimmune rheumatic diseases. Our findings emphasize the important role of nurses in providing nonpharmacological strategies to help patients better manage their disease and improve health outcomes.